Menelaah Gerakan Modernis-Reformis Islam melalui Kota Gede: Pembacaan Seorang Antropolog Jepang - Latief, Hilman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2013)
The first Indonesian edition of this book was published in 1983. The publishing of second edition reflects a profound engagement of Nakamura with his research subjects among the Muhammadiyah members in Kota Gede-Yogyakarta for nearly four decades. The book also symbolizes the author’s thoughtful contribution to Indonesian studies in general, and the study of Indonesian Muslim societies in particular. The book has a clear argument about the role of the Islamic reformist movement in a certain kind of Islamization process in Java. More importantly it has opened more space and opportunities for younger researchers to dig further different patterns and complexities of the modernist movement that can be discovered in the field.DOI: 10.15408/sdi.v20i2.391